Pengaruh Current Ratio, Debt to Equity Ratio, dan perputaran aktiva tetap terhadap Return On Asset - Citarayani, Irma; Saputro, Rizky Arif (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Companies make money by doing business. All company operations are funded by profits. where company profits are used to finance all company operational activities and company investments. This study aims to examine the effect of the current ratio (CR), debt-to-equity ratio (DER), and fixed asset turnover (FATO). This study uses a quantitative method, which in this study uses data on the annual financial statements of telecommunications sub-sector companies for the years 2013–2020 from certain samples and selective sampling. Five companies met the research requirements. This study uses multilinear regression. The results showed that the current ratio has a large effect on return on assets, the debt-to-equity ratio has no effect and is not significant, and fixed asset turnover has a significant negative effect. The R2 value was corrected by 0.904 (90.4%), meaning that all independent factors influenced the dependent variable by 90.4% while other variables had an effect of 9.6%.